Students’ Perceptions towards Using Mobile Application in Learning Speaking - Desika Rinanda; Suparno Suparno; Sri Samiati Tarjana (Hasanuddin University, 2019)
The dramatic advancement technologies, particularly mobile applications, have influenced the education sector. The integration of mobile applications in education to change the teaching-learning process has taken place and led to innovative learning, including English language learning. Hence, this study aimed to find out the students’ perceptions and the factors influencing students’ perceptions toward the use of mobile application in learning English particularly speaking. To reach the objectives, this study used case study as the research method. The data were collected mainly through interview and observation. The participants were five vocational school students in Surakarta, Central Java, Indonesia. They were purposively selected because they had been familiar with mobile application and they had been taught speaking English using mobile application by their teacher, so that they could give adequate information. The research findings showed positive perception from the students toward the use of Learn English Conversation application in learning speaking. They declared that the use of Learn English Conversation application could facilitate them in practicing speaking, bring fun and enjoyable learning during the learning process. Moreover, their positive perceptions were influenced by several factors such as the flexibility and the new learning experience given by the mobile application, the ease to run the mobile application and unrequired a lot of internet quota when the students run the mobile application.